Bimbingan Tahsin Intensif: Peningkatan Penguasaan Hukum Tajwid Pada Anak “Maghrib Mengaji” Di Lingkungan Masjid Al Madinah Deli Tua - Zuhri, Mutiara; Zahriani, Nurul (Journal of Community Sustainability, 2026)
The Maghrib Mengaji (Quran Recitation) program is a mosque-based religious program designed to develop a generation that understands the Quran from a young age. However, many children still struggle to read the Quran according to the correct rules of tajweed. Based on preliminary research at the Al Madinah Mosque in Deli Tua, most children do not fully understand the rules of mad (inflection), ghunnah (inflection), and proper pronunciation of letters. Therefore, an Intensive Tahsin Guidance program was held as part of the Community Service Program (PKM) to improve Quran reading skills and foster religious enthusiasm among children in the mosque area. The implementation method consisted of preparation, implementation, mentoring, and evaluation. This two-week program involved hands-on practice, drills, demonstrations, and individual assessments. The results of this program showed a significant improvement in the children's tajweed skills: 80% of participants were able to read with the correct rules of tajweed, an increase from only 20% before the program. This program also has a positive impact on developing religious character, including discipline, politeness, and a love for the Quran.